A preparation method of high temperature resistant concrete based on elementi
A cross-linked calcium aluminum sulfate CAS expansion agent enhances the high-temperature resistance and mechanical properties of concrete, addressing cracking and deformation issues in thermal equipment, while reducing fiber usage and costs.
Patent Information
- Application Number
- CN202410509922.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-04-26
AI Technical Summary
Existing high-temperature resistant concretes used in thermal equipment and industrial kilns suffer from cracking, high-temperature powdering, and deformation, failing to maintain mechanical properties under extreme temperatures.
A high-temperature resistant concrete formulation using cross-linked calcium aluminum sulfate CAS expansion agent with silicon-oxygen bonds, combined with mullite and basalt fibers, to enhance structural integrity and mechanical strength.
The concrete maintains good compressive, flexural, and impact strength under high temperatures, reducing the need for excessive high-temperature resistant fibers and lowering production costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of concrete modification and preparation, and in particular relates to a preparation method of elementi-based high temperature resistant concrete. Background Art
[0002] At present, the GRC (glass fiber reinforced concrete) industry generally uses silicate cement-based or sulphoaluminate cement-based concrete as the main raw material for production, because of its advantages such as low cost and easy operation. However, with the upgrading and iteration of products, the original operation mode can no longer meet higher quality and usage requirements. For example, in thermal equipment, industrial kilns and structures subjected to high temperatures, high-temperature resistant concrete is required, and its products require GRC products to be able to be used for a long time in a temperature environment of 200 to 500 degrees Celsius. However, most factories still use the old operation mode and formula ratio (such as increasing the use of high-temperature resistant fibers, etc.), resulting in a variety of serious quality problems (such as cracking of concrete at high temperatures, high-temperature powdering and deformation, etc.).
[0003] Therefore, it is of practical application value to study a high-temperature resistant concrete that has high temperature resistance, does not crack and differentiate, and still maintains high mechanical properties. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention obtains a cross-linked calcium aluminum sulfate CAS expansion agent by cross-linking and modifying the CAS expansion agent, so that the CAS expansion agent has a high-temperature resistant silicon-oxygen bond structure, and then applies it to the preparation of concrete, which not only improves the high-temperature resistance of the concrete, but also the network structure formed by covalent cross-linking enables the concrete to still maintain good compressive, flexural and impact strength under high temperature resistance, which is used to solve the problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents:
[0005] A high temperature resistant concrete based on elementi, the high temperature resistant concrete comprises the following raw materials in parts by weight:
[0006] 20-30 parts of acrylic emulsion, 30-40 parts of sulphoaluminate cement, 15-20 parts of cross-linked calcium aluminum sulfate CAS expansion agent, 5-10 parts of anhydrite, 5-10 parts of quartz sand, 20-25 parts of mullite aggregate, 10-15 parts of barite aggregate, 0.2-0.5 parts of waterproofing agent, 0.1-0.4 parts of thickener, 0.5-1 parts of defoaming agent, 1-1.5 parts of water reducing agent, 2-5 parts of nano-grade glass fiber and 3-5 parts of basalt fiber.
[0007] Preferably, the concrete comprises the following raw materials in parts by weight:
[0008] 20 parts of acrylic emulsion, 30 parts of sulphoaluminate cement, 20 parts of cross-linked calcium aluminum sulfate CAS expansion agent, 10 parts of anhydrite, 10 parts of quartz sand, 20 parts of mullite aggregate, 10 parts of barite aggregate, 0.2 parts of waterproofing agent, 0.1 parts of thickener, 0.5 parts of defoaming agent, 1 part of water reducing agent, 2 parts of nano-grade glass fiber and 3 parts of basalt fiber.
[0009] Furthermore, the sulphoaluminate cement is sulphoaluminate cement with a grade of 42.5.
[0010] Furthermore, the preparation method of the cross-linked calcium aluminum sulfate CAS expansion agent comprises the following steps:
[0011] Silane coupling agent: ethanol: deionized water are mixed in a mass ratio of 1:2:5, and then heated to 40-50°C for reaction for 4 hours, and after removing ethanol and water by vacuum distillation, a hydroxy acrylate polymer having the same mass as the silane coupling agent is added to form a reaction liquid, and after adding an inorganic base to the reaction liquid, the reaction liquid is heated to 90-110°C for reaction to obtain reactant 1;
[0012] Calcium sulfate is dissolved in an ammonium salt solution and mixed with an equal mass of the reactant 1 and stirred for 10 to 12 hours, and vacuum dried at 55° C. for 16 to 18 hours to obtain a reactant 2;
[0013] The reactant 2 is mixed with aluminum oxide, calcium oxide and a boron-containing substance and ground to obtain a raw material. The raw material is pressed into a cake, calcined and cooled to room temperature to obtain the cross-linked calcium aluminum sulfate CAS expansion agent.
[0014] Furthermore, the silane coupling agent is a silane coupling agent containing an ester structure, and the silane coupling agent containing an ester structure includes KH-570.
[0015] Furthermore, the preparation method of the hydroxyacrylate polymer comprises the following steps:
[0016] After mixing the hydroxy acrylate monomer and ammonium persulfate, dimethyl sulfoxide is added to form a reaction system, the reaction system is heated to 60-80° C. and reacted for 3-4 hours to obtain the hydroxy acrylate polymer;
[0017] The amount of the ammonium persulfate added is 0.01 to 0.02 times the weight of the hydroxy acrylate monomer, and the amount of the dimethyl sulfoxide added is 1 to 2 times the weight of the hydroxy acrylate monomer.
[0018] Furthermore, the hydroxyacrylate monomer includes hydroxyethyl acrylate or hydroxypropyl acrylate.
[0019] Furthermore, the ammonium salt solution includes ammonium chloride.
[0020] Furthermore, the mass ratio of the reactant 2:aluminum oxide:calcium oxide is 1:3:3, and the amount of the boron-containing compound used is 0.5-6% of the total mass of the reactant 2, aluminum oxide and calcium oxide.
[0021] Furthermore, the boron-containing substance includes boron oxide.
[0022] Furthermore, the mullite aggregate can be purchased from the market, or can be synthesized from high-purity kaolin and industrial alumina calcined at 1000° C. as raw materials, with some ZnO, talc and zircon sand added as additives to produce low-cost, high-purity mullite aggregate.
[0023] A preparation method based on elementi high temperature resistant concrete, the preparation method comprising the following steps:
[0024] Put acrylic emulsion, sulphoaluminate cement, cross-linked calcium aluminum sulfate CAS expansion agent, anhydrite, quartz sand, mullite aggregate, barite aggregate, waterproofing agent, thickener, defoamer, water reducing agent and basalt fiber into a mixer, rotate the mixer at 2800 rpm, rotate forward for 5 to 10 minutes and then reverse for 5 to 10 minutes to obtain a mixture 1;
[0025] The mixture 1 is injected into a screw pump, and then nano-scale glass fibers are added and mixed therewith and stirred continuously to obtain the high temperature resistant concrete.
[0026] Furthermore, the waterproofing agent is sodium methyl silicate, the thickener is gum arabic, the defoaming agent is polyoxypropylene oxyethylene glycerol ether, and the water reducing agent is SR-7302.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) In the present invention, silanol groups obtained by hydrolysis of a silane coupling agent are covalently cross-linked with a hydroxyacrylate polymer having multiple hydroxy groups on the side chain to form a siloxane bond having multiple high-temperature resistant structures. The silane coupling agent and the hydroxyacrylate are cross-linked by metal coordination between oxygen atoms having lone electron pairs on the ester structure and calcium ions in dissolved calcium sulfate, respectively, to prepare a cross-linked calcium aluminum sulfate CAS expansion agent. The concrete prepared by the cross-linked calcium aluminum sulfate CAS expansion agent has a synergistic coordination of a network structure formed by multiple cross-linking, so that the concrete finally prepared not only has good high-temperature resistance, but also has high mechanical properties.
[0029] (2) By using cross-linked calcium aluminum sulfate (CAS) expansion agent with high-temperature resistant silicon-oxygen bonds and metal coordination effects, the use of high-temperature resistant fibers such as mullite aggregate and basalt fiber is reduced, thereby reducing the production cost of concrete. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0031] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.
[0032] Preparation Example 1:
[0033] The preparation of hydroxy acrylate polymer includes the following steps:
[0034] 2 kg of hydroxyethyl acrylate was weighed and put into a reactor, and 2 kg of dimethyl sulfoxide and 20 g of ammonium persulfate were added and mixed. After the reactor was replaced with nitrogen, the temperature was raised to 60° C. and reacted for 3 hours to obtain a hydroxy acrylate polymer.
[0035] Preparation Example 2:
[0036] The preparation of hydroxy acrylate polymer includes the following steps:
[0037] 2 kg of hydroxyethyl acrylate was weighed and put into a reactor, and 3 kg of dimethyl sulfoxide and 28 g of ammonium persulfate were added and mixed. After the reactor was replaced with nitrogen, the temperature was raised to 70° C. and reacted for 3 hours to obtain a hydroxy acrylate polymer.
[0038] Preparation Example 3:
[0039] The preparation of hydroxy acrylate polymer includes the following steps:
[0040] 2 kg of hydroxypropyl acrylate was weighed and put into a reactor, and 4 kg of dimethyl sulfoxide and 40 g of ammonium persulfate were added and mixed. After the reactor was replaced with nitrogen, the temperature was raised to 80° C. and reacted for 3 hours to obtain a hydroxy acrylate polymer.
[0041] Preparation Example 4:
[0042] The preparation of cross-linked calcium aluminum sulfate CAS expansion agent includes the following steps:
[0043] 1 kg of KH-570, 2 kg of ethanol and 5 kg of deionized water were mixed and stirred evenly, and then heated in a water bath to 40° C. and then started timing. After reacting for 4 hours, ethanol and water were removed by vacuum distillation, and the remaining solution was mixed with 1 kg of the hydroxy acrylate polymer in Preparation Example 1 to form a reaction system. 100 g of sodium hydroxide was added to the reaction system, and the reaction system was heated to 90° C. and reacted for 3 hours to obtain reactant 1;
[0044] After dissolving 1 kg of calcium sulfate in 1 kg of ammonium chloride solution, 1 kg of reactant 1 and 1 kg of dissolved calcium sulfate were weighed and mixed for 10 hours, and then vacuum dried at 55° C. for 16 hours to obtain reactant 2;
[0045] 1 kg of reactant 2, 3 kg of aluminum oxide, 3 kg of calcium oxide and 35 g of boron oxide were mixed, ground into raw material by a pulverizer, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain a cross-linked calcium aluminum sulfate CAS expansion agent.
[0046] Preparation Example 5:
[0047] The preparation of cross-linked calcium aluminum sulfate CAS expansion agent includes the following steps:
[0048] 1 kg of KH-570, 2 kg of ethanol and 5 kg of deionized water were mixed and stirred evenly, and then heated in a water bath to 45° C. and then timing was started. After reacting for 4 hours, ethanol and water were removed by vacuum distillation, and the remaining solution was mixed with 1 kg of the hydroxy acrylate polymer in Preparation Example 2 to form a reaction system. 100 g of potassium hydroxide was added to the reaction system, and the reaction system was heated to 100° C. and reacted for 3 hours to obtain reactant 1;
[0049] After dissolving 1 kg of calcium sulfate with 2 kg of ammonium chloride solution, 1 kg of reactant 1 and 1 kg of dissolved calcium sulfate were respectively weighed and mixed for 11 hours, and then vacuum dried at 55°C for 17 hours to obtain reactant 2;
[0050] 1 kg of reactant 2, 3 kg of aluminum oxide, 3 kg of calcium oxide and 140 g of boron oxide were mixed, ground into raw material by a pulverizer, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain a cross-linked calcium aluminum sulfate CAS expansion agent.
[0051] Preparation Example 6:
[0052] The preparation of cross-linked calcium aluminum sulfate CAS expansion agent includes the following steps:
[0053] 1 kg of KH-570, 2 kg of ethanol and 5 kg of deionized water were mixed and stirred evenly, and then heated in a water bath to 50° C. and then the timing was started. After reacting for 4 hours, the ethanol and water were removed by vacuum distillation, and the remaining solution was mixed with 1 kg of the hydroxy acrylate polymer in Preparation Example 3 to form a reaction system. 100 g of potassium hydroxide was added to the reaction system, and the reaction system was heated to 110° C. and reacted for 3 hours to obtain reactant 1;
[0054] After dissolving 1 kg of calcium sulfate with 2 kg of ammonium chloride solution, 1 kg of reactant 1 and 1 kg of dissolved calcium sulfate were respectively weighed and mixed for 12 hours, and then vacuum dried at 55°C for 18 hours to obtain reactant 2;
[0055] 1 kg of reactant 2, 3 kg of aluminum oxide, 3 kg of calcium oxide and 420 g of boron oxide were mixed, ground into raw material by a pulverizer, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain a cross-linked calcium aluminum sulfate CAS expansion agent.
[0056] Embodiment 1:
[0057] A preparation method of elementi-based high temperature resistant concrete, the specific process includes the following steps:
[0058] 20 parts by weight of acrylic emulsion, 30 parts by weight of 42.5 grade sulphoaluminate cement, 20 parts by weight of the cross-linked calcium aluminum sulfate CAS expansion agent of Preparation Example 4, 10 parts by weight of anhydrite, 10 parts by weight of quartz sand, 20 parts by weight of mullite aggregate, 10 parts by weight of barite aggregate, 0.2 parts by weight of sodium methyl silicate, 0.1 parts by weight of gum arabic, 0.5 parts by weight of polyoxypropylene oxyethylene glycerol ether, 1 part by weight of SR-7302 and 3 parts by weight of basalt fiber were put into a mixer, the mixer was rotated at 2800 rpm, and then reversed for 5 minutes after being forwardly rotated for 5 minutes; then the mixed materials were injected into a screw pump, and 2 parts by weight of nano-grade glass fiber were added and mixed with the mixture and stirred continuously to obtain high temperature resistant concrete.
[0059] Embodiment 2:
[0060] A preparation method of elementi-based high temperature resistant concrete, the specific process includes the following steps:
[0061] 25 parts by weight of acrylic emulsion, 35 parts by weight of 42.5 grade sulphoaluminate cement, 17 parts by weight of cross-linked calcium aluminum sulfate CAS expansion agent of Preparation Example 5, 8 parts by weight of anhydrite, 8 parts by weight of quartz sand, 23 parts by weight of mullite aggregate, 12 parts by weight of barite aggregate, 0.4 parts by weight of sodium methyl silicate, 0.2 parts by weight of gum arabic, 0.7 parts by weight of polyoxypropylene oxyethylene glycerol ether, 1.2 parts by weight of SR-7302 and 4 parts by weight of basalt fiber were put into a mixer, the mixer was rotated at 2800 rpm, and then reversed for 7 minutes after being forwardly rotated for 7 minutes; then the mixed materials were injected into a screw pump, and 4 parts by weight of nano-grade glass fiber were added and mixed with the mixture and stirred continuously to obtain high temperature resistant concrete.
[0062] Embodiment 3:
[0063] A preparation method of elementi-based high temperature resistant concrete, the specific process includes the following steps:
[0064] 30 parts by weight of acrylic emulsion, 40 parts by weight of 42.5 grade sulphoaluminate cement, 15 parts by weight of cross-linked calcium aluminum sulfate CAS expansion agent of Preparation Example 6, 5 parts by weight of anhydrite, 5 parts by weight of quartz sand, 25 parts by weight of mullite aggregate, 15 parts by weight of barite aggregate, 0.5 parts by weight of sodium methyl silicate, 0.4 parts by weight of gum arabic, 1 part by weight of polyoxypropylene oxyethylene glycerol ether, 1.5 parts by weight of SR-7302 and 5 parts by weight of basalt fiber were put into a mixer, the mixer was rotated at 2800 rpm, and then reversed for 10 minutes after being forwardly rotated for 10 minutes; then the mixed materials were injected into a screw pump, and 5 parts by weight of nano-grade glass fiber were added and mixed with it and stirred continuously to obtain high temperature resistant concrete.
[0065] Comparative Example 1:
[0066] Step S1, preparation of CAS expansion agent:
[0067] 1kg of calcium sulfate, 3kg of aluminum oxide, 3kg of calcium oxide and 35g of boron oxide are mixed and ground, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain CAS expansion agent;
[0068] Step S2: Preparation of concrete:
[0069] The difference from Example 1 is that the cross-linked calcium aluminum sulfate CAS expansion agent is replaced with the CAS expansion agent prepared in step S1, and the mullite aggregate is increased to 40 parts by weight and the basalt fiber is increased to 10 parts by weight, while the other conditions remain unchanged.
[0070] Comparative Example 2:
[0071] Step S1, preparation of CAS expansion agent:
[0072] 1kg of calcium sulfate, 3kg of aluminum oxide, 3kg of calcium oxide and 140g of boron oxide are mixed and ground, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain CAS expansion agent;
[0073] Step S2: Preparation of concrete:
[0074] The difference from Example 2 is that the cross-linked calcium aluminum sulfate CAS expansion agent is replaced with the CAS expansion agent prepared in step S1, and the mullite aggregate is increased to 45 parts by weight and the basalt fiber is increased to 15 parts by weight, while the other conditions remain unchanged.
[0075] Comparative Example 3:
[0076] Step S1, preparation of CAS expansion agent:
[0077] 1kg of calcium sulfate, 3kg of aluminum oxide, 3kg of calcium oxide and 420g of boron oxide are mixed and ground, pressed into cakes, calcined at high temperature and then naturally cooled to room temperature to obtain CAS expansion agent;
[0078] Step S2: Preparation of concrete:
[0079] The difference from Example 3 is that the cross-linked calcium aluminum sulfate CAS expansion agent is replaced with the CAS expansion agent prepared in step S1, and the mullite aggregate is increased to 50 parts by weight and the basalt fiber is increased to 20 parts by weight, while the other conditions remain unchanged.
[0080] The high temperature resistant concretes of Examples 1 to 3 and the concretes of Comparative Examples 1 to 3 were tested for high temperature resistant mechanical properties at 500±5°C. The results are shown in the following table:
[0081] High temperature resistance mechanical properties test results table
[0082]
[0083]
[0084]
[0085]
[0086] It can be seen from the data in the above table that the high temperature resistant concrete of Examples 1 to 3 has no undesirable phenomena such as cracking and delamination on the surface before and after high temperature treatment, and the retention rates of compressive strength, impact strength and flexural strength after high temperature treatment are better than those of Comparative Examples 1 to 3, indicating that the high temperature resistant concrete prepared by the present invention can maintain good mechanical properties while having high temperature resistance.
[0087] The above-described embodiments are compared with the technical solutions and beneficial effects of the present invention, and it should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A high temperature resistant concrete based on elementi, characterized in that, The high temperature resistant concrete comprises the following raw materials in parts by weight: 20~30 parts of acrylic emulsion, 30~40 parts of sulphoaluminate cement, 15~20 parts of cross-linked calcium aluminum sulfate CAS expansion agent, 5~10 parts of anhydrite, 5~10 parts of quartz sand, 20~25 parts of mullite aggregate, 10~15 parts of barite aggregate, 0.2~0.5 parts of waterproofing agent, 0.1~0.4 parts of thickener, 0.5~1 parts of defoaming agent, 1~1.5 parts of water reducing agent, 2~5 parts of nano-grade glass fiber and 3~5 parts of basalt fiber; The preparation method of the cross-linked calcium aluminum sulfate CAS expansion agent comprises the following steps: Silane coupling agent: ethanol: deionized water are mixed in a mass ratio of 1:2:5, and then heated to 40-50°C for reaction for 4 hours. After removing ethanol and water by vacuum distillation, a hydroxy acrylate polymer having the same mass as the silane coupling agent is added to form a reaction liquid. After adding an inorganic base to the reaction liquid, the reaction liquid is heated to 90-110°C for reaction to obtain reactant 1; Calcium sulfate is dissolved in an ammonium salt solution and mixed with an equal mass of the reactant 1 and stirred for 10-12 hours, and vacuum dried at 55° C. for 16-18 hours to obtain a reactant 2; The reactant 2 is mixed with aluminum oxide, calcium oxide and a boron-containing substance and ground to obtain a raw material, and the raw material is pressed into a cake, calcined and cooled to room temperature to obtain the cross-linked calcium aluminum sulfate CAS expansion agent; The silane coupling agent is a silane coupling agent containing an ester structure, and the silane coupling agent containing an ester structure includes KH-570; The preparation method of the hydroxyacrylate polymer comprises the following steps: After mixing the hydroxy acrylate monomer and ammonium persulfate, dimethyl sulfoxide is added to form a reaction system, the reaction system is heated to 60-80° C. and reacted for 3-4 hours to obtain the hydroxy acrylate polymer; The amount of ammonium persulfate added is 0.01 to 0.02 times the weight of the hydroxy acrylate monomer, and the amount of dimethyl sulfoxide added is 1 to 2 times the weight of the hydroxy acrylate monomer; The hydroxy acrylate monomer includes hydroxyethyl acrylate or hydroxypropyl acrylate; The ammonium salt solution includes ammonium chloride; The mass ratio of the reactant 2:alumina:calcium oxide is 1:3:3, and the amount of the boron-containing compound used is 0.5-6% of the total mass of the reactant 2, alumina and calcium oxide; The boron-containing substance includes boron oxide.
2. A method for preparing high temperature resistant concrete based on elementi as claimed in claim 1, characterized in that: The preparation method comprises the following steps: Put acrylic emulsion, sulphoaluminate cement, cross-linked calcium aluminum sulfate CAS expansion agent, anhydrite, quartz sand, mullite aggregate, barite aggregate, waterproofing agent, thickener, defoamer, water reducing agent and basalt fiber into a mixer, rotate the mixer at 2800 rpm, rotate forward for 5-10 minutes and then reverse for 5-10 minutes to obtain a mixture 1; The mixture 1 is injected into a screw pump, and then nano-scale glass fibers are added and mixed therewith and stirred continuously to obtain the high temperature resistant concrete.